PENERAPAN PRICE LIMIT UNTUK MENGATASI VOLATILITAS RETURN SAHAM - Maria Rio Rita; Rendhy Bramantha Wisudana (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
Some stock markets have employed a number of circuit breakers to avoid non-rational overreaction and price limit is one of them. While price limit is widely accepted benchmarks for the prevention of market crash, the question of weather price limit reduces stock price volatility has long attracted research interest. The purpose of this study is to test volatility spillover hypothesis by examining Indonesia Stock Exchange price limit system. We use LQ-45 stocks data from August 2001-January 2002, while research period begins from 3 December 2001- 31 December 2006. The evidence supports that all hypotheses suggesting that price limit may be effective to reduce volatility.